Relational contracts and job design - Anja Schöttner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper analyzes the problem of optimal job design when there is only one contractible and imperfect performance measure for all tasks whose contribution to firm value is non-verifiable. I find that task splitting is optimal when relational contracts based on firm value are not feasible. By contrast, if an agent who performs a given set of tasks receives an implicit bonus, the principal always benefits from assigning an additional task to this agent.
Keywords: M51; M54; 330; job design; multi-tasking; relational contracts